2010
DOI: 10.1261/rna.1960410
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C virus genomic RNA dimerization is mediated via a kissing complex intermediate

Abstract: With over 200 million people infected with hepatitis C virus (HCV) worldwide, there is a need for more effective and bettertolerated therapeutic strategies. The HCV genome is a positive-sense; single-stranded RNA encoding a large polyprotein cleaved at multiple sites to produce at least ten proteins, among them an error-prone RNA polymerase that confers a high mutation rate. Despite considerable overall sequence diversity, in the 39-untranslated region of the HCV genomic RNA there is a 98-nucleotide (nt) seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
114
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(121 citation statements)
references
References 59 publications
7
114
0
Order By: Relevance
“…In another work, the authors showed that the RNA dimerization would be mediated via a kissing complex intermediate between two structurally rearranged DLS. The core protein would then stabilize the resulting extended duplex (Shetty et al 2010). Our results show that the minimal structured motif of the 3 ′ UTR containing the dimer linkage sequence SL2 is able to dimerize in vitro in the absence of any added protein.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…In another work, the authors showed that the RNA dimerization would be mediated via a kissing complex intermediate between two structurally rearranged DLS. The core protein would then stabilize the resulting extended duplex (Shetty et al 2010). Our results show that the minimal structured motif of the 3 ′ UTR containing the dimer linkage sequence SL2 is able to dimerize in vitro in the absence of any added protein.…”
Section: Discussionmentioning
confidence: 81%
“…Previous works suggested that SL2 could be responsible for the dimerization of the viral RNA (Ivanyi-Nagy et al 2006;Shetty et al 2010). The results obtained with SL2 also prompted us to further investigate this stem-loop structure that displays a palindromic sequence.…”
Section: Self-association Of Sl2mentioning
confidence: 90%
“…Formation of the terminal 3 ′ SLI and the known upstream stem-loop that includes the dimer linkage sequence (DLS) ( Fig. 4A; Ivanyi-Nagy et al 2006;Shetty et al 2010 . Alignment based secondary structures of the X-tail using sequences of 19 isolates.…”
Section: X-tailmentioning
confidence: 99%
“…In an alternative conformation of the X-tail, only two stem-loops are formed. Here, SLI remains the same, but SLII and SLIII are merged to form a single stemloop which includes a so-called dimerization linkage sequence (DLS) in its apical loop that was proposed to be necessary for viral RNA genome dimerization and possibly for genome encapsidation (Ivanyi-Nagy et al 2006;Shetty et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…HCV is a single stranded positive sense RNA virus belongs to the genus hepacivirus of Flaviviridae family [1]. It has a single open reading genome of ~9.6 kb, encoding a polypeptide of 3010 amino acids, flanked by untranslated region at both 5ʹ and 3ʹ terminus [2].…”
Section: Introductionmentioning
confidence: 99%